2010
DOI: 10.3109/10428194.2010.538777
|View full text |Cite
|
Sign up to set email alerts
|

T-cell-depleted allogeneic transplant without donor leukocyte infusions results in excellent long-term survival in patients with multiply relapsed Lymphoma. Predictors for survival after transplant relapse

Abstract: We analyzed 67 patients with lymphoma who received alemtuzumab-based conditioning regimens for allogeneic stem cell transplant and no post-transplant DLI. The median age was 54 (24–70), 43% had unrelated donors, 34% had chemotherapy refractory disease, and 25% had an elevated LDH. With a median follow-up for survivors of 35 months, the estimated 3-year progression-free survival (PFS) and overall survival (OS) were 30% and 47%, respectively. Chemosensitivity by CT and pre-transplant LDH were independent prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…In univariate analysis, prior HDT-ASCT negatively impacted OS and PFS, elevated LDH at time of allo-SCT was prognostic for OS, and patients with HCT-CI ≥ 3 trended toward reduced OS and PFS (p=0.1). LDH above normal prior to allo-SCT has been previously identified by others to be a poor-prognostic feature in both alemtuzumab containing [32] and non- in vivo T cell depleted RIC allo-SCT [29]. HCT-CI ≥ 3 has reached prognostic significance in other RIC allo-SCT series for patients with lymphoid malignancies [33, 34].…”
Section: Discussionmentioning
confidence: 98%
“…In univariate analysis, prior HDT-ASCT negatively impacted OS and PFS, elevated LDH at time of allo-SCT was prognostic for OS, and patients with HCT-CI ≥ 3 trended toward reduced OS and PFS (p=0.1). LDH above normal prior to allo-SCT has been previously identified by others to be a poor-prognostic feature in both alemtuzumab containing [32] and non- in vivo T cell depleted RIC allo-SCT [29]. HCT-CI ≥ 3 has reached prognostic significance in other RIC allo-SCT series for patients with lymphoid malignancies [33, 34].…”
Section: Discussionmentioning
confidence: 98%
“…Those who fail to respond to chemotherapy and come to transplant without radiologic response or with an elevated LDH are unlikely to do well; only a small fraction will be cured. 26;32;39;58;83;84 By contrast, several investigators find that findings of PET positivity have no impact for response to allogeneic transplant. 39;85 Patients with partial responses to salvage and normal LDH but residual PET positive areas may be good candidates for allogeneic transplant.…”
Section: Allogeneic Transplantation For Recurrent or Refractory Intermentioning
confidence: 98%
“…41;44 Avoidance of late chronic GVHD underlies our interest, and that of other groups in T-cell depleted transplant,usually using in vivo alemtuzumab or ATG. 36;38;39;45 Many studies, usually non randomized have compared the outcomes of T-depleted transplant and, with few exceptions have shown a somewhat increased rate of disease recurrence but no effect on survival. 4648 Some studies, using profound in-vitro T-cell depletion have however shown a very high early recurrence rate.…”
Section: Gvhd Prophylaxismentioning
confidence: 99%
See 2 more Smart Citations